2020
DOI: 10.1186/s12967-020-02259-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of NGS-based liquid biopsy in untreated late stage non-squamous lung carcinoma in a single institution

Abstract: Background: NGS from plasma samples in non-squamous cell lung carcinoma (NSCC) can aid in the detection of actionable genomic alterations. However, the absolute clinical value of NGS in liquid biopsy (LB) made at baseline is currently uncertain. We assessed the impact of plasma-based NGS using an in-house test and an outsourced test in comparison to a routine molecular pathology workflow. Methods: Twenty-four advanced/metastatic treatment-naïve NSCC patients were prospectively included. NGS analyses were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…They are based on the testing of blood or other body fluids (for example, the aqueous humour) and constitute an alternative reproducible method to the classical tissue biopsy, which can be used to detect circulating tumour DNA (ctDNA), circulating tumour cells (CTCs), exosomes, cytokines and microRNAs, among other components [ 298 , 300 , 301 ]. LBs have been particularly promising in different solid tumours, including lung cancer, with some studies demonstrating encouraging results in their usage in the daily practice [ 302 , 303 ], despite some current technical limitations [ 304 , 305 , 306 ]. In UM, the LB technology is not yet as developed as it is for other types of cancers and there are no currently available LB systems approved by both the European Medicines Agency (EMA) and Food and Drug Administration (FDA) [ 298 ].…”
Section: Current Challenges and Future Perspectives In Uveal Melanomamentioning
confidence: 99%
“…They are based on the testing of blood or other body fluids (for example, the aqueous humour) and constitute an alternative reproducible method to the classical tissue biopsy, which can be used to detect circulating tumour DNA (ctDNA), circulating tumour cells (CTCs), exosomes, cytokines and microRNAs, among other components [ 298 , 300 , 301 ]. LBs have been particularly promising in different solid tumours, including lung cancer, with some studies demonstrating encouraging results in their usage in the daily practice [ 302 , 303 ], despite some current technical limitations [ 304 , 305 , 306 ]. In UM, the LB technology is not yet as developed as it is for other types of cancers and there are no currently available LB systems approved by both the European Medicines Agency (EMA) and Food and Drug Administration (FDA) [ 298 ].…”
Section: Current Challenges and Future Perspectives In Uveal Melanomamentioning
confidence: 99%
“…A few other studies investigated NGS for detection of genomic alterations at diagnosis used blood from late stage NSCLC patients [ 44 , 45 , 46 ]. A study on a limited number of 21 NSCLC patients compared an in-house analysis with a limited panel of 11 genes (Oncomine, ThermoFisher Scientific, Waltham, MA, USA) and an outsource analysis with a panel of 70 genes (Foundation Medicine, Cambridge, MA, USA) [ 45 ]. This study showed a high level of concordance of detected genomic alterations in the common genes present in these two panels, but a shorter TAT to obtain the results when using the in-house approach [ 45 ].…”
Section: Ngs With Blood Samples At Diagnosis Of Advanced Non-small Cell Lung Carcinomamentioning
confidence: 99%
“…A study on a limited number of 21 NSCLC patients compared an in-house analysis with a limited panel of 11 genes (Oncomine, ThermoFisher Scientific, Waltham, MA, USA) and an outsource analysis with a panel of 70 genes (Foundation Medicine, Cambridge, MA, USA) [ 45 ]. This study showed a high level of concordance of detected genomic alterations in the common genes present in these two panels, but a shorter TAT to obtain the results when using the in-house approach [ 45 ]. A study was performed with a customized NGS panel (called SiRe) including six genes [ EGFR, KRAS, NRAS (NRAS Proto-Oncogene, GTPase), BRAF, KIT Proto-Oncogene Receptor Tyrosine Kinase (KIT)), Platelet-Derived Growth Factor Receptor Alpha (PDGFRA) ] for 194 patients with advanced adenocarcinomas [ 46 ].…”
Section: Ngs With Blood Samples At Diagnosis Of Advanced Non-small Cell Lung Carcinomamentioning
confidence: 99%
“…NGS can be applied for targeted gene panels, whole exome sequencing and whole genome sequencing, and provides a resolution to single-base precision while permitting large amounts of DNA fragments to be sequenced simultaneously and independently [43][44][45][46]. It is also used in new diagnostic concepts such as liquid biopsy assays [47,48], and was shown to be suitable in routine clinical practice for this application [49,50]. Furthermore, it is used to test for emerging biomarkers in cancer treatment such as Microsatellite instability and Tumor mutation burden, which are predictive for immunotherapy response [51,52].…”
Section: Sequencing-based Techniquesmentioning
confidence: 99%